CHILDREN’S FOLKLORE IN EASTERN SUMBA, INDONESIA - Retang Wohangara (Universitas 17 Agustus 1945 Semarang, 2020)
Children’s folklore is common in all cultures. During childhood, children engage in activities to build friendship, have fun, and above all to develop particular life qualities. Though children’s folklore did not quite attract folklorist’s interest in the early development of folklore studies, now, it has become an attracting arena of interests for many social scientists. This research attempts to give a descriptive analysis of the children’s folklore, i.e. games, in eastern Sumba, Indonesia. The invasive presence of technology certainly affects the existence of “old-time” children’s folklore. Children of the present are heavily exposed to “modern games” that overpower the vitality of the traditional games. Some people see this shift as something inevitable, and the only way to respond to this situation is by accepting this “game revolution.” However, some old-time game supporters attempt to revitalize the old-time children folklore by holding events where children’s traditional games are performed. The latter believe that maintaining children folklore is of importance because it is a matter of identity, and above all, children’s modern games cannot replace the social values offered by the traditional ones. This present article, written based on the data from interviews and discussions on social media, aims to list some traditional games in eastern Sumba. Like any other children in other parts of the world, Sumbanese children are also friendly with modern games. Yet, some still perform the “old time” games. In addition, this article also gives some description of each game and the values the participants might learn from the children’s folklore. Key words: folklore, children’s folklore, eastern Sumba